The Baby Dragon Bookshop - Qureshi, A. T., 1999- (Qureshi, A. T., 1999- Baby Dragon series, 2026)
"Emmy has an enemy, and his name is Luke. The good news? She rarely sees him. The bad news? When she does, she (and her pet dragons) are reminded just how handsome he is. Besides, Emmy is too busy focusing on her dragon-fuelled business to have time for love. But when both she and Luke approach the same local investor for funding, she's suddenly unable to avoid him. The kooky investor insists they must compete for the cash by working at the local failing baby dragon bookshop to prove their magical business knowledge"--